Positive Self-Talk on Pain Intensity and Pain Interference in Low Back Pain Patients - Rumbun Sirait; Jenny Marlindawani Purba; Ikhsanuddin A Harahap (Universitas Aisyah Pringsewu, 2022)
Low back pain (LBP) is a musculoskeletal disorder that can cause pain and limit activity in patients. Pain experienced by LBP patients has an impact on pain interference. This seems to be directly proportional, where the result of the pain felt gives discomfort to the patients and affects aspects of life. One of the non-pharmacological to reduce pain is positive self-talk. The study aimed to determine the effect of positive self-talk on pain intensity and pain interference in LBP patients. The study was quasi-experimental with an equivalent control group approach. Forty respondents were selected by consecutive sampling. Data were analyzed using a paired t-test. The results show that there was a significant difference between pain intensity (p-value 0.000) and pain interference (p-value 0.000) before and after positive self-talk intervention. Meanwhile, there was a significant difference between pain intensity (p-value 0.00) however there was no significant difference between pain interference (p-value 0.06) before and after the standard hospital procedural intervention. Furthermore, based on the results of the independent t-test, shows that there was a significant difference between pain intensity (p-value 0.0001) and pain interference (p-value 0.004) after being given positive self-talk intervention. It is recommended that positive self-talk can be given as a non-pharmacological approach t reduce pain intensity and interference in LBP patients. Abstrak: Low back pain (LBP) merupakan gangguan muskuloskletal yang dapat menimbulkan nyeri dan membatasi aktivitas pada pasien. Nyeri yang dialami oleh pasien LBP berdampak pada gangguan nyeri. Hal ini tampaknya secara langsung proporsional, dimana akibat dari nyeri yang dirasakan memberikan ketidaknyamanan pada pasien dan mempengaruhi aspek kehidupan. Salah satu cara nonfarmakologi untuk mengurangi nyeri adalah self-talk positif. Penelitian ini bertujuan untuk mengetahui pengaruh positive self-talk terhadap intensitas nyeri dan gangguan nyeri pada pasien LBP. Penelitian ini merupakan eksperimen semu dengan pendekatan kelompok kontrol yang setara. Empat puluh responden dipilih secara Consecutive Sampling. Data dianalisis menggunakan uji t berpasangan. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara intensitas nyeri (p value 0,000) dan gangguan nyeri (p value 0,000) sebelum dan sesudah intervensi self-talk positif. Sementara itu, ada perbedaan yang signifikan antara intensitas nyeri (p value 0,00) namun tidak ada perbedaan yang signifikan antara gangguan nyeri (p value 0,06) sebelum dan sesudah intervensi prosedur standar rumah sakit. Selanjutnya berdasarkan hasil uji independent t-test menunjukkan bahwa terdapat perbedaan yang signifikan antara intensitas nyeri (p value 0,0001) dan gangguan nyeri (p value 0,004) setelah diberikan intervensi self-talk positif. Direkomendasikan bahwa positive self talk dapat diberikan sebagai pendekatan non farmakologi untuk mengurangi intensitas nyeri dan gangguan paten LBP.